Perantau Manggarai di Kelurahan Sesetan Kecamatan Denpasar Selatan - Asmi, Fredieman; Kaler, I Ketut; Suarsana, I Nyoman (Humanis, 2018)
This study aims to determine the implementation of IKMB in Sesetan Village, South Denpasar District. The theoretical frameworks and concepts used to support the theory of adaptation, assimilation theory and conceptual framework related to overseas culture for Manggarai people who live in the area or temporarily in Sesetan Village, South Denpasar Subdistrict. The method and technique of this research is divided into three, namely 1) methods and techniques in the form of participant observation and interview; 2) literature study method; And 3) data analysis techniques. The results obtained from the above research on the Manggarai family inhabiting on the island of Bali as a family existence that closely maintains each component of its own culture as well as in the Overseas lands as manifestations that mutually support each other by generating multicultural cultures and languages.